Analisis Proses Pembelajaran Siswa Berbasis Online Di Kelas Rendah Pada Masa Pandemic Covid-19 - Redita Wiguna; Astri Sutisnawati; Dyah Lyesmaya (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study describes the online-based learning process during the Covid-19 pandemic that began in March 2020, because Indonesia is one of the countries affected by this pandemic. This caused Indonesia to call for work from home and online learning to slow down the spread of Covid-19. Online based learning used in this study is learning that utilizes the use of Whatsapp in information communication tools. The presentation in this article is part of qualitative research report description whose main focus is to look at the learning process carried out online during the Covid-19 pandemic. The result showed that there are factors that greatly influence the learning process when carried out online. In this case, Whatsapp-assisted online learning experiences several obstacles to the learning process of student in elementary schools.